2019
DOI: 10.1111/gcb.14545
|View full text |Cite
|
Sign up to set email alerts
|

Role of host genetics and heat‐tolerant algal symbionts in sustaining populations of the endangered coral Orbicella faveolata in the Florida Keys with ocean warming

Abstract: Identifying which factors lead to coral bleaching resistance is a priority given the global decline of coral reefs with ocean warming. During the second year of back‐to‐back bleaching events in the Florida Keys in 2014 and 2015, we characterized key environmental and biological factors associated with bleaching resilience in the threatened reef‐building coral Orbicella faveolata. Ten reefs (five inshore, five offshore, 179 corals total) were sampled during bleaching (September 2015) and recovery (May 2016). Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
142
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 88 publications
13
142
1
Order By: Relevance
“…In this study, Symbiodiniaceae community composition in A. millepora was more strongly structured by the host (or biotic interactions) than imposed by the environment (Figures 5 and 6). Similar to this finding, Manzello et al (2019) reported that 73% of the distribution of D.…”
Section: Symbiont Diversity Is Not Strongly Associated With Stressosupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, Symbiodiniaceae community composition in A. millepora was more strongly structured by the host (or biotic interactions) than imposed by the environment (Figures 5 and 6). Similar to this finding, Manzello et al (2019) reported that 73% of the distribution of D.…”
Section: Symbiont Diversity Is Not Strongly Associated With Stressosupporting
confidence: 80%
“…Microbial symbionts can influence the capacity of their reef-building coral hosts to acclimatize and adapt to environmental stressors. In particular, dinoflagellates in the Family Symbiodiniaceae (including genera Symbiodinium, Breviolum, Cladocopium, and Durusdinium;LaJeunesse et al, 2018) reside in the tissues of corals, giant clams, and other marine invertebrates, and have been empirically shown to influence the ability of corals to survive stress events (e.g., Baker, 2001Baker, , 2004Cunning & Baker, 2013;Kenkel & Bay, 2018;LaJeunesse, Smith, Finney, & Oxenford, 2009;Manzello et al, 2019;Rouze, Lecellier, Saulnier, & Berteaux-Lecellier, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Third, there are tradeoffs associated with tolerant symbionts that impact holobiont physiology under benign conditions (Cantin, van Oppen, Willis, Mieog, & Negri, 2009;Cunning, Gillette, Capo, Galvez, & Baker, 2015;Jones & Berkelmans, 2011;Little, Van Oppen, & Willis, 2004). Finally, recent evidence shows the host genotype explains a substantial amount of the variation in symbiont communities (Manzello et al, 2019;Quigley, Warner, Bay, & Willis, 2018;Quigley, Willis, & Bay, 2017), amplifying its importance for the tolerance of the holobiont.…”
Section: Introductionmentioning
confidence: 99%
“…Early observations using self‐recognition assays documented clonality among neighbors and, occasionally, colonies separated by tens of meters of substrate (Neigel & Avise, ). Genetic markers also document clonality of massive morphologies, suggesting that fragmentation is common for multiple species on Caribbean reefs (Foster, Baums, & Mumby, ; Foster et al, ; Manzello et al, ; Studivan & Voss, ). However, previous work shows that genetic diversity in A. cervicornis is present and variable over small spatial scales such as individual reefs, meaning that sexual reproduction and recruitment are also important drivers of contemporary populations (Drury et al, ; Reyes & Schizas, ; Vollmer & Palumbi, ).…”
Section: Introductionmentioning
confidence: 99%